Beginning Android 2 - Murphy, Mark L.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
The Android development platform, created by Google and the Open Handset Alliance, is a platform in its truest sense, encompassing hundreds of classes beyond the traditional Java classes and open source components that ship with the SDK. With Beginning Android 2, you$1 (Bll learn how to develop applications for Android 2.x mobile devices, using simple examples that are ready to run with your copy of the software development kit. Author, Android columnist, writer, developer, and community advocate Mark L. Murphy will show you what you need to know to get started programming Android applications, including how to craft graphical user interfaces, use GPS, and access web services.s
The Big Picture -- Projects and Targets -- Creating a Skeleton Application -- Using XML-Based Layouts -- Employing Basic Widgets -- Working with Containers -- Using Selection Widgets -- Getting Fancy with Lists -- Employing Fancy Widgets and Containers -- The Input Method Framework -- Applying Menus -- Fonts -- Embedding the WebKit Browser -- Showing Pop-Up Messages -- Dealing with Threads -- Handling Activity Life Cycle Events -- Creating Intent Filters -- Launching Activities and Subactivities -- Handling Rotation -- Working with Resources -- Using Preferences -- Managing and Accessing Local Databases -- Accessing Files -- Leveraging Java Libraries -- Communicating via the Internet -- Using a Content Provider -- Building a Content Provider -- Requesting and Requiring Permissions -- Creating a Service -- Invoking a Service -- Alerting Users via Notifications -- Accessing Location-Based Services -- Mapping with MapView and MapActivity -- Handling Telephone Calls -- Development Tools -- Handling Multiple Screen Sizes -- Dealing with Devices -- Handling Platform Changes -- Where Do We Go from Here?.
Keywords: Computer science; Computer Science; Programming Techniques